Property loss and cultural heritage restoration in the aftermath of genocide: understanding harm and conceptualising repair - Hickey, Robin (International journal of transitional justice, 2021)
This article seeks to contribute a ‘thicker’ understanding of the harm caused by the destruction of cultural heritage and the means through which that harm can be redressed. It analyses attacks on property of local significance to the Cham, an Islamic group subjected to religious persecution and genocide during the Khmer Rouge regime in Cambodia. Using Bernadette Atuahene’s property-loss concepts of ‘dignity takings’ and ‘dignity restoration,’ the article links the loss of property associated with the group’s cultural heritage to experiences of dehumanization, infantilization and community destruction. The article explores how responses to the Cham’s loss of cultural heritage have been iterative, at times unintentional and ultimately unsuccessful in redressing the full impacts of the loss. It stresses the importance of moving beyond a focus on specific restitution to develop a spectrum of interventions which reaffirm victims’ humanity, reinforce their agency and allow them to reconnect meaningfully with their heritage.